Effect of weather parameters on the population dynamics of White backed planthopper, Sogatella furcifera (Horvath) in rice - Anand Kumar, ADVSLP; Mallikharjuna Rao, N; Rama Rao, CV; Krishnam Raju, S (ORYZA-An International Journal of Rice, 2021)
A field experiment on the population dynamics of White backed planthopper (WBPH), Sogatella furcifera (Horvath) carried out during kharif and rabi 2016-17 at Regional Agricultural Research Station, Maruteru, West Godavari District of Andhra Pradesh, India revealed that the incidence of WBPH was observed during 36th SMW (September 3-9). Its activity increased during successive weeks up to 44th SMW with two peaks, first peak at 38th SMW (September 17-23) with population of 46/10 hills and second peak at 42nd SMW (October 15-21) with population of 170/ 10 hills during kharif 2016, while WBPH was first noticed during 7th SMW (February 12-18) and population increased gradually during successive weeks and attained peak number during 13th SMW (March 26-April 1) in rabi 2016-17. Correlation studies revealed that WBPH had significant negative relation with morning relative humidity of current week during kharif 2016. None of the abiotic factors has showed significant relationship with the population of WBPH during rabi 2016-17.